Nanoscale pore characteristics of the Jurassic Dongyuemiao member lacustrine shale, Eastern Sichuan Basin, SW China: Insights from SEM, NMR, LTNA, and MICP experiments - Zhou, Yadong; Wang, Zhanlei; Hu, Dongfeng; Wei, Zhihong; Wei, Xiangfeng; Liu, Ruobing; Wang, Daojun; Jiang, Yuqiang (Frontiers in Earth Science, 2023)
The Jurassic Dongyuemiao Member is the most promising target for breakthrough in lacustrine shale gas exploration in Sichuan Basin. Integrating SEM, NMR, LTNA, MICP experiments and other basic measurements, the nanoscale pore category, structure and corresponding controlling factors of Dongyuemiao lacustrine shale in Eastern Sichuan Basin are studied. The results indicate that organic pores is comprised of primary pores within plant debris and secondary pores within bitumen. The inorganic pore is composed of intraparticle pore within calcite particle, intercrystalline pore between pyrite crystals, and interparticle pore between different minerals. The 4th Section lacustrine shale of Dongyuemiao Member has the best pore structure, exhibiting higher organic pore proportion, larger amount of gas adsorption, and parallel plate-shaped pore morphology. The micropores (<2nm) are the main contributor of PV and SA of Dongyuemiao lacustrine shale. The enrichment of organic matter has a positive effect on the formation of micropores and has no influence on the mesopore-macropore (>2nm). The quartz has no significant effect on the formation of nanoscale pores. The intraparticle pores within calcite particles constitute part of mesopore-macropore, but not micropores. Clay minerals are conducive to the formation of micropores, but play a negative role in the formation of mesopore-macropores.